Human-specific changes in two functional enhancers of FOXP2 : Evolution of FOXP2 enhancers - Benítez-Burraco, Antonio; Torres-Ruiz, Raúl; Gelabert, Pere; Lalueza-Fox, Carles; Rodríguez-Perales, Sandra; García-Bellido, Paloma (Cellular and Molecular Biology, 2022)
FOXP2 is a gene involved in language development and function. Neanderthals and humans share the same coding region of the gene, although the formers are thought to have exhibited less sophisticated language abilities. In this paper, we report on several human-specific changes in two functional enhancers of FOXP2. Two of these variants are located within the binding sites for the transcription factors POLR2A and SMARCC1, respectively. Interestingly, SMARCC1 is involved in brain development and vitamin D metabolism. We hypothesize that the human specific change in this position might have resulted in a different regulation pattern of FOXP2 expression in our species compared to extinct hominins, with a potential impact on our language abilities.